Impact of Tourism Accommodation Development Towards the Social Cultural Aspects in Kisoro District. - Aineryoona, Alex (Kabale University, 2024)
The study focused on evaluating the impact of tourism accommodation development on socio-cultural aspects in Kisoro District. It was guided by three objectives: identifying the different types of accommodation facilities in Kisoro District, determining the socio-cultural aspects in the area, and examining the relationship between accommodation facilities and socio-cultural aspects. The target population consisted of 52 respondents, including senior staff, managers, and community members. The study employed both simple random sampling and purposive sampling techniques to select the sample. Data were collected using questionnaires, observations, and interviews, then edited, coded, and analyzed using Microsoft Excel, with the results presented in tables. The findings revealed various types of accommodation in Kisoro District, such as apartments, resorts, motels, hostels, guest houses, holiday cottages, and hotels. Regarding socio-cultural aspects, the study identified factors such as family, religion, peers, social norms and values, and media as influential in the district. The study also established a positive relationship between accommodation facilities and socio-cultural aspects, with a beta value of .543, indicating that a 54.3% improvement in accommodation could lead to enhanced socio-cultural aspects. The findings concluded by listing the different accommodation options available in Kisoro District, including apartments, resorts, motels, hostels, guest houses, holiday cottages, and hotels.